Pengaruh Kepemimpinan Adaptif dan Self Control terhadap Keterlibatan Kerja Barista - Davita Variani; Luthfi Noor Aini (Jurnal Riset Psikologi, 2026)
Abstract.This study aims to examine the influence of adaptive leadership and self-control on baristas’ job involvement. Adaptive leadership refers to a leader’s ability to respond flexibly to situational demands, adjust approaches, navigate conflicting demands, and adapt behaviour to the complexity of the work environment. Self-control is defined as the ability to regulate emotions, impulses, and actions in alignment with long-term goals, while job involvement reflects a condition in which individuals are cognitively, emotionally, and behaviourally fully engaged in their work. This study employed a quantitative approach with an explanatory research design involving 115 baristas selected through purposive sampling. The instruments used were the Adaptive Leadership Behaviour Scale, the Short Self-control Scale, and the job involvement scale developed by Kanungo. The results of multiple linear regression analysis indicate that adaptive leadership has a significant effect on job involvement (p = 0.000), and self-control also has a significant effect (p = 0.000). Simultaneously, both variables show a significant effect on job involvement, with an F value of 211.479 and p = 0.000. The R² value of 0.791 indicates that 79.1% of the variance in job involvement can be explained by adaptive leadership and self-control. However, violations of the assumptions of normality, multicollinearity, and heteroscedasticity were found; therefore, the interpretation of the model should be approached with caution. Overall, this study highlights the important role of adaptive leadership and self-control in enhancing baristas’ job involvement.Abstrak. Studi ini bertujuan untuk menganalisis pengaruh kepemimpinan adaptif, dan self-control terhadap keterlibatan kerja barista. Gaya kepemimpinan adaptif merujuk pada kemampuan pemimpin merespons kebutuhan situasi secara fleksibel, mengubah pendekatan, menavigasi tuntutan yang kontradiktif, dan menyesuaikan perilaku dengan kompleksitas lingkungan kerja, self-control merupakan kemampuan mengatur emosi, impuls, dan tindakan agar selaras dengan tujuan jangka panjang sedangkan keterlibatan kerja merupakan kondisi ketika individu secara kognitif, emosional, dan perilaku terlibat sepenuhnya dalam pekerjaannya. Studi ini menggunakan pendekatan kuantitatif desain eksplanatori dengan 115 barista sebagai responden yang dipilih melalui teknik purposive sampling. Instrumen meliputi Adaptive Leadership Behavior Scale, Short Self-control Scale, skala keterlibatan kerja dari Kanungo.  Hasil analisis regresi linier berganda menunjukkan bahwa gaya kepemimpinan adaptif berpengaruh signifikan terhadap keterlibatan kerja barista (p = 0,000), demikian pula self-control memiliki pengaruh signifikan (p = 0,000). Secara simultan, kedua variabel juga menunjukkan pengaruh yang signifikan terhadap keterlibatan kerja dengan nilai F = 211,479 dan p = 0,000. Nilai R² sebesar 0,791 mengindikasikan bahwa 79,1% variasi keterlibatan kerja dapat dijelaskan oleh gaya kepemimpinan adaptif dan self-control. Meskipun demikian, terdapat pelanggaran pada asumsi normalitas, multikolinearitas, dan heteroskedastisitas sehingga interpretasi model perlu dilakukan secara hati-hati. Secara keseluruhan, studi ini menegaskan pentingnya peran kepemimpinan adaptif dan kontrol diri dalam meningkatkan keterlibatan kerja barista.